Controversies in the Management of Endometrial Cancer - V. Masciullo; G. Amadio; D. Lo Russo; I. Raimondo; A. Giordano; G. Scambia (Obstetrics and Gynecology International)
Endometrial cancer (EC) remains the most common malignancy of the female genital tract. The median age at diagnosis is the sixth decade, with abnormal uterine bleeding at the presentation in 90% of the patients. Surgical treatment, including complete hysterectomy, removal of remaining adnexal structures, and an appropriate surgical staging, represents the milestone of curative therapy for patients with EC. Adjuvant therapy is necessary in patients at high risk of recurrence. Conservative treatment approaches should be used in selected cases for women with a desire of fertility preservation. This review summarizes the management of EC and discusses current controversies regarding the role of lymphadenectomy and radiotherapy in patients with intermediate-risk tumors confined to the uterus.